Influence of Outdoor Source on The Variations of Indoor PM2.5 Concentration and Its Morphological Properties in Roadside School Environment - Suroto, Azrin (International Journal of Integrated Engineering, 2019)
Particles with aerodynamic diameters equal or less than 2.5 µm, which are known as fine particles (PM2.5), are major air pollutants that could seriously impact ambient and indoor air quality. The air quality in school environments less than 500 m away from the roadside is potentially affected by vehicles through exhaust emissions. Thus, the concentrations of ambient and indoor fine particles (PM2.5) were measured using a portable outdoor beta-attenuation monitor and an optical indoor direct reading monitor in two naturally ventilated school environments for 8 h during the teaching and learning sessions. In addition, meteorological parameters such as temperature, relative humidity and wind speed were measured under ambient and indoor conditions. PM2.5 samples were also collected and morphologically characterised. Pearson’s correlation was applied to identify the relationship between the ambient and indoor conditions of PM2.5, temperature, relative humidity and wind speed. Results showed that the indoor and outdoor PM2.5 in selected schools were varied. The concentration of indoor PM2.5 was higher than that of outdoor PM2.5 in both schools. Pearson’s correlation showed a significant correlation between indoor and outdoor PM2.5 in schools A (p = 0.006, r = 0.54) and B (p = 0.001, r = 0.74). In addition, ambient temperature, relative humidity and wind speed are the important factors that affect the outdoor concentrations of PM2.5.